Apoptotic Molecules In Chronic Leukemia (Bangladesh Journal of Medical Science, 2016)
Background: Chronic myeloid leukemia (CML) is characterized by the spread of malignant cells that exhibit resistance to caspase-mediated cell death (apoptosis) and this mechanism is proposed to play an important role in myeloid cell growth. However, the extent to which caspase-mediated cell death plays a crucial role in the regulation of myelopoiesis remains controversial.Objectives & Proceedure: The objectives of this study were to examine whether or not caspase-mediated cell death-related proteins take part in the development of CML and to also to detect the relationship between Fas, p53 and caspase-mediated cell death protease activating factor (Apaf-1) in 5 patients with CML using the real-time quantitative polymerase chain reaction. We demonstratedthatp53 and Apaf-1 messenger ribonucleic acid (mRNA) expression was moderately elevated (up to 5 fold, p